Negative pole piece, secondary battery and electronic device
By adding specific compounds to the negative electrode material layer of the lithium-ion battery, a stable double-layer SEI structure is formed, which solves the electrolyte consumption and interface film rupture caused by the charge and discharge of silicon-based materials, and improves the cycling performance and other dynamic performance of the battery.
Patent Information
- Application Number
- CN202411997265.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-22
AI Technical Summary
In lithium-ion batteries, when silicon-based materials are used as negative electrode active materials, they will cause volume expansion and contraction during charging and discharging, resulting in continuous consumption of electrolyte and repeated rupture of the interface film, thereby reducing the circulating performance of the battery.
The first compound is added to the negative electrode material layer so that there are infrared characteristic peaks within a specific infrared spectrum range, thereby forming an inner layer of artificial SEI film, and adjusting the deposition of the outer layer of natural SEI film to form a stable bilayer SEI structure.
The interface stability between the negative electrode sheet and the electrolyte is improved, the side reaction between the negative electrode active material and the electrolyte is reduced, the continuous consumption of the electrolyte is reduced, and the kinetics, high temperature performance, thermal safety performance and cycling performance of the secondary battery are improved.
Smart Images

Figure CN119864362A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a negative electrode sheet, a secondary battery and an electronic device. Background Art
[0002] Lithium-ion batteries have significant advantages such as high energy density, miniaturization and light weight, and are widely used in mobile phones, laptops, tablets, drones, electric vehicles, power tools, power storage systems, etc.
[0003] At present, the negative electrode active material of commercial secondary batteries is still mainly graphite. However, the lithium insertion capacity of graphite is about 372mAh / g, while the lithium insertion capacity of silicon as the negative electrode active material can reach 3579mAh / g. Silicon can achieve a higher energy density of secondary batteries, that is, store more energy under the same volume and weight. However, compared with graphite, when silicon-based materials are used as negative electrode active materials, they will undergo greater volume expansion and contraction during the charge and discharge process, causing the solid-electrolyte interface film (SEI) formed by the electrolyte on the negative electrode surface to repeatedly rupture and regenerate, resulting in continuous consumption of electrolyte components, and ultimately leading to a significant reduction in the cycle performance of lithium-ion batteries. Summary of the invention
[0004] The purpose of the present application is to provide a negative electrode plate, a secondary battery and an electronic device to improve the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte during the cycle process, and improving the kinetics, high temperature performance, thermal safety and cycle performance of the secondary battery.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the negative electrode material layer comprises a negative electrode active material and a first compound, and the infrared spectrum of the negative electrode material layer is 1050cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm -1 and 1730cm -1 Up to 1750cm -1 By adding the first compound to the negative electrode material layer, the negative electrode material layer has an infrared characteristic peak at 1050cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm-1 and 1730cm -1 Up to 1750cm -1 There is an infrared characteristic peak between them. During the secondary battery cycle, an inner artificial SEI film can be formed on the surface of the negative electrode. + In the process of continuous embedding / ejection, it is beneficial to regulate the deposition of the outer natural SEI film, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial and outer natural on the negative electrode material layer, improving the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, and effectively reducing the continuous consumption of the electrolyte. Therefore, the secondary battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0007] In some embodiments of the present application, the first compound includes a compound of formula I:
[0008]
[0009] R is selected from substituted or unsubstituted C1-C6 alkyl; when substituted, the substituent of the alkyl is halogen, amino or hydroxyl. The first compound within the above range is selected to facilitate electrochemical reaction, and the secondary battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0010] In some embodiments of the present application, the negative electrode active material includes silicon and carbon, and the mass percentage of silicon is A, 0.1%≤A≤10%, based on the sum of the mass of silicon and carbon in the negative electrode active material; and / or, based on the mass of the negative electrode material layer, the mass percentage of the first compound is B, 2%≤B≤5%; preferably, 2%≤B≤3%. By regulating the mass percentage of silicon A and / or the mass percentage of the first compound B within the above range, the secondary battery has a higher energy density while improving the kinetics, high temperature performance, thermal safety performance and cycle performance.
[0011] In some embodiments of the present application, 1≤B / A≤20. By regulating the value of B / A within the above range, the kinetics, high temperature performance, thermal safety performance and cycle performance of the secondary battery are improved while having a higher energy density.
[0012] In some embodiments of the present application, the compound of formula I includes at least one of the following compounds:
[0013]
[0014] In some embodiments of the present application, the negative electrode active material further comprises at least one of natural graphite or artificial graphite. By selecting the above-mentioned negative electrode active materials, the structural stability of the negative electrode sheet can be improved while taking into account the energy density of the secondary battery.
[0015] In some embodiments of the present application, the negative electrode material layer also includes a binder, and the binder includes at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyamide-imide, styrene-butadiene rubber, polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral or aqueous acrylic resin, and the mass percentage of the binder is C, 0.65%≤C≤2.4% based on the mass of the negative electrode material layer. By selecting the above-mentioned types of binders and regulating the mass percentage of the binder within the above range, the mechanical strength of the negative electrode plate is improved, so that the secondary battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0016] The second aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a separator, an electrolyte, and a negative electrode sheet in any of the above embodiments. The secondary battery of the present application has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0017] In some embodiments of the present application, the electrolyte includes a second compound, the second compound includes vinyl sulfate and / or 1,3-propane sultone, and the mass percentage of the second compound is D based on the mass of the electrolyte, 0.01%≤D≤2%. By adding the above-mentioned second compound of the type to the electrolyte and regulating the mass percentage D of the second compound within the above range, the first compound and the second compound act synergistically, thereby improving the kinetics, high temperature performance, thermal safety performance and cycle performance of the secondary battery.
[0018] In some embodiments of the present application, the electrolyte includes a third compound, the third compound includes methylene disulfonate and / or vinylene carbonate, and the mass percentage of the third compound is E, 0.01%≤E≤2% based on the mass of the electrolyte. By adding the third compound of the above type to the electrolyte and regulating the mass percentage E of the third compound within the above range, it is beneficial to form a more stable SEI film during the charge and discharge process of the secondary battery, the first compound and the third compound act synergistically, and the secondary battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0019] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0020] Beneficial effects of this application:
[0021] The present application provides a negative electrode plate, a secondary battery and an electronic device. The negative electrode plate includes a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material and a first compound. The infrared spectrum of the negative electrode material layer is 1050cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm -1 and 1730cm -1 Up to 1750cm -1 By adding the first compound to the negative electrode material layer, the negative electrode material layer has an infrared characteristic peak at 1050cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm -1 and 1730cm -1 Up to 1750cm -1 There is an infrared characteristic peak between them. During the secondary battery cycle, an inner artificial SEI film can be formed on the surface of the negative electrode. + In the process of continuous embedding / ejection, it is beneficial to regulate the deposition of the outer natural SEI film, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial and outer natural on the negative electrode material layer, improving the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, and effectively reducing the continuous consumption of the electrolyte. Therefore, the secondary battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0022] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and a person skilled in the art can also obtain other embodiments based on these drawings.
[0024] Figure 1 is the infrared spectrum of the first compound of formula I-1. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0026] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0027] The first aspect of the present application provides a negative electrode plate, the negative electrode plate comprises a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the negative electrode material layer comprises a negative electrode active material and a first compound, and the infrared spectrum of the negative electrode material layer is 1050cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm -1 and 1730cm -1 Up to 1750cm -1 There are infrared characteristic peaks in between.
[0028] The inventors have found that during the charge and discharge process of the secondary battery, the volume of the negative electrode plate will expand and shrink, causing the SEI film of the electrolyte on the surface of the negative electrode plate to break and form repeatedly. Especially when the negative electrode material layer contains silicon, the volume expansion and contraction of the negative electrode plate is more obvious, and the electrolyte is consumed too much, which affects the dynamic performance of the secondary battery. When the first compound is added to the negative electrode material layer, the infrared spectrum of the negative electrode material layer has a peak at 1050cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm -1 and 1730cm -1 Up to 1750cm -1 There is an infrared characteristic peak between them. At this time, the negative electrode material layer includes CO, C=C and C=O groups. During the secondary battery cycle, the compounds including the above groups can form an inner layer of artificial SEI film on the surface of the negative electrode. + In the process of continuous embedding / ejection, it is beneficial to regulate the deposition of the outer natural SEI film, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial and outer natural layers on the negative electrode material layer, improving the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, and effectively reducing the continuous consumption of the electrolyte, thereby improving the capacity attenuation of the secondary battery caused by excessive thickening of the natural SEI film; in addition, the artificial SEI film has high ionic conductivity and mechanical stability, which is beneficial to improving the diffusion path of lithium ions in the SEI film, and thus, the secondary battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0029] The above-mentioned "negative electrode material layer located on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be located on one surface of the negative electrode current collector along its thickness direction, or on two surfaces of the negative electrode current collector along its thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode current collector, or it can be a partial area of the surface of the negative electrode current collector. This application is not particularly limited, as long as the purpose of this application can be achieved.
[0030] In some embodiments of the present application, the first compound includes a compound of formula I:
[0031]
[0032] R is selected from substituted or unsubstituted C1-C6 alkyl; when substituted, the substituent of the alkyl is halogen, amino or hydroxy. The halogen can be -F, -Cl, -Br or -I.
[0033] The first compound selected within the above range is conducive to the occurrence of electrochemical reactions. During the secondary battery cycle, the first compound decomposes in the electrolyte to form compounds including CO, C=C and C=O groups, which can form an inner layer of artificial SEI film. + The continuous embedding / ejection process is beneficial to regulate the deposition of the outer natural SEI film, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial and outer natural layers on the negative electrode material layer, improving the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, and reducing the continuous consumption of the electrolyte, thereby improving the capacity attenuation of the secondary battery caused by excessive thickening of the natural SEI film; in addition, the artificial SEI film has high ionic conductivity and mechanical stability, which is beneficial to improving the diffusion path of lithium ions in the SEI film, and thus the secondary battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0034] In some embodiments of the present application, the negative electrode active material includes silicon and carbon. Based on the sum of the masses of silicon and carbon in the negative electrode active material, the mass percentage of silicon is A, 0.1%≤A≤10%, for example, the value of A can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of the values. By regulating the mass percentage content A of silicon within the above range, silicon has a higher theoretical specific capacity, and adding silicon within the above content range to the negative electrode material layer is beneficial to improving the energy density of the secondary battery.
[0035] In some embodiments of the present application, based on the mass of the negative electrode material layer, the mass percentage of the first compound is B, 2%≤B≤5%; preferably, 2%≤B≤3%. For example, the value of B can be 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, or a range consisting of any two of these values. Regulating the mass percentage B of the first compound within the above range is beneficial to regulating the deposition of the outer natural SEI film, and the first compound can be decomposed in the electrolyte to form compounds with certain chemical stability and ion conductivity including groups such as CO, C=C and C=O, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial and outer natural on the negative electrode material layer, improving the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, and reducing the continuous consumption of the electrolyte. In addition, the artificial SEI film has high ionic conductivity and mechanical stability. Therefore, while having a higher energy density, it improves the kinetics, high temperature performance, thermal safety performance and cycle performance of the secondary battery.
[0036] In some embodiments of the present application, the negative electrode active material includes silicon and carbon. Based on the sum of the mass of silicon and carbon in the negative electrode active material, the mass percentage of silicon is A, 0.1%≤A≤10%, for example, the value of A can be 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any two of the values. And, based on the mass of the negative electrode material layer, the mass percentage of the first compound is B, 2%≤B≤5%; preferably, 2%≤B≤3%. For example, the value of B can be 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, or a range consisting of any two of the values. By regulating the mass percentage A of silicon element and the mass percentage B of the first compound within the above range, silicon has a higher theoretical specific capacity. Adding silicon element within the above content range to the negative electrode material layer is beneficial to improving the energy density of the secondary battery. Adding the first compound within the above content range is beneficial to regulating the deposition of the outer natural SEI film, and the first compound can decompose and react in the electrolyte, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial and outer natural on the negative electrode material layer, improving the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, and reducing the continuous consumption of the electrolyte. In addition, the artificial SEI film has high ionic conductivity and mechanical stability. Therefore, while having a higher energy density, the kinetics, high temperature performance, thermal safety performance and cycle performance of the secondary battery are improved.
[0037] In some embodiments of the present application, the negative electrode active material includes a silicon-based material, and the silicon-based material includes at least one of elemental silicon, silicon carbide compound, or SiO x where 0 < x ≤ 2. By regulating the above types of silicon-based materials, silicon itself has a relatively high theoretical specific capacity. Adding the above types of silicon-based materials to the negative electrode material layer is beneficial to improving the energy density of the secondary battery.
[0038] In some embodiments of the present application, 0.2 ≤ B / A ≤ 50. For example, the value of B / A can be 0.2, 0.5, 0.8, 1, 3, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48, 50 or a range composed of any two of these values. When the negative electrode material layer contains silicon elements, the degree of volume expansion and contraction of the negative electrode plate during the cycling process is relatively obvious. By regulating the value of B / A within the above range, a relatively stable and uniform double-layer SEI structure of artificial inner layer and natural outer layer is formed on the negative electrode material layer, and the effect of improving the interfacial stability between the negative electrode plate and the electrolyte is more significant, thereby reducing the side reaction between the negative electrode active material and the electrolyte and reducing the continuous consumption of the electrolyte. In addition, the artificial SEI film has high ionic conductivity and mechanical stability. Therefore, while having a relatively high energy density, the kinetics, high-temperature performance, thermal safety performance, and cycling performance of the secondary battery are improved.
[0039] In some embodiments of the present application, 1 ≤ B / A ≤ 20. For example, the value of B / A can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or a range composed of any two of these values. By regulating the value of B / A within the above range, when the negative electrode material layer contains silicon elements, the degree of volume expansion and contraction of the negative electrode plate during the cycling process is relatively obvious. By regulating the value of B / A within the above range, the silicon element and the first compound act synergistically to form a relatively stable and uniform double-layer SEI structure of artificial inner layer and natural outer layer on the negative electrode material layer, and the effect of improving the interfacial stability between the negative electrode plate and the electrolyte is more significant, thereby reducing the side reaction between the negative electrode active material and the electrolyte and reducing the continuous consumption of the electrolyte, and improving the high-temperature performance of the secondary battery. In addition, the artificial SEI film has high ionic conductivity and mechanical stability. Therefore, while having a relatively high energy density, the kinetics, high-temperature performance, thermal safety performance, and cycling performance of the secondary battery are improved.
[0040] In some embodiments of the present application, the compound of formula I includes at least one of the following compounds:
[0041]
[0042] For example, Figure 1 The infrared spectrum of the first compound of formula I-1 is shown in Figure 1. -1 、1650cm -1 and 1735cm -1 There is an infrared characteristic peak at the negative electrode material layer. At this time, the negative electrode material layer includes CO, C=C and C=O groups. During the secondary battery cycle, the compounds including the above groups can form an inner layer of artificial SEI film on the surface of the negative electrode. + In the process of continuous embedding / ejection, it is beneficial to regulate the deposition of the outer natural SEI film, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial layer and outer natural layer on the negative electrode material layer. + The continuous embedding / ejection process is beneficial to regulate the deposition of the outer natural SEI film, thereby forming a relatively stable and uniform double-layer SEI structure of inner artificial and outer natural layers on the negative electrode material layer, improving the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, and reducing the continuous consumption of the electrolyte, thereby improving the capacity attenuation of the secondary battery caused by excessive thickening of the natural SEI film; in addition, the artificial SEI film has high ionic conductivity and mechanical stability, which is beneficial to improving the diffusion path of lithium ions in the SEI film, and thus the secondary battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0043] In some embodiments of the present application, the negative electrode active material also includes at least one of natural graphite or artificial graphite. By selecting the above-mentioned types of negative electrode active materials, while taking into account the energy density of the secondary battery, it is beneficial to improve the structural stability of the negative electrode sheet, so that the secondary battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0044] In some embodiments of the present application, the negative electrode material layer further includes a binder, and the binder includes at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyamide-imide, styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB) or aqueous acrylic resin, and the mass percentage of the binder is C based on the mass of the negative electrode material layer, 0.65%≤C≤2.4%. For example, the value of C can be 0.65%, 0.68%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4% or a range consisting of any two of the values. By selecting the above-mentioned types of binders and regulating the mass percentage of the binder within the above-mentioned range, the first compound is combined with the negative electrode binder so that the binder forms a relatively stable chemical bond on the surface of the negative electrode plate, which is beneficial to enhancing the bonding strength between the negative electrode active materials and between the negative electrode active materials and the negative electrode collector, thereby improving the mechanical strength of the negative electrode plate. Therefore, the secondary battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0045] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it can contain copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or composite current collector. For example, the composite current collector can be a lithium copper composite current collector, a carbon copper composite current collector, a nickel copper composite current collector, a titanium copper composite current collector, etc. In the present application, the negative electrode material layer also includes a negative electrode conductive agent. The present application has no particular restrictions on the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can include but is not limited to conductive carbon black (Super P), carbon nanotubes (CNT), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. At least one of conductive carbon black can include but is not limited to acetylene black or Ketjen black. The above-mentioned carbon nanotubes can include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers can include but are not limited to vapor-grown carbon fibers (VGCF) and / or nanocarbon fibers. The above-mentioned metal materials can include but are not limited to metal powders and / or metal fibers. Specifically, the metal can include but is not limited to at least one of copper, nickel, aluminum or silver. The conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. In the present application, the negative electrode material layer also includes a thickener, and the present application has no particular restrictions on the thickener, as long as the purpose of the present application can be achieved. For example, the thickener may include but is not limited to carboxymethyl cellulose (CMC) or sodium carboxymethyl cellulose (CMC-Na).
[0046] The present application has no particular restrictions on the preparation method of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the negative electrode sheet includes but is not limited to the following steps: (1) mixing the negative electrode active material, the first compound, the binder, the negative electrode conductive agent, and the thickener in a certain mass ratio and adding a solvent to prepare a negative electrode slurry; (2) coating the negative electrode slurry on one surface of the negative electrode collector, and drying to obtain a negative electrode sheet with a single-sided negative electrode material layer; (3) repeating the above steps on the other surface of the negative electrode collector to obtain a negative electrode sheet with a double-sided negative electrode material layer; (4) cold pressing, cutting, and slitting to obtain a negative electrode sheet.
[0047] In the present application, the mass percentage of silicon in the negative electrode active material can be regulated by regulating the proportion of silicon-based materials in the negative electrode active material. In the present application, the mass percentage of the first compound in the negative electrode material layer and the mass percentage of the negative electrode binder in the negative electrode material layer can be regulated by regulating the mass ratio of the negative electrode active material, the first compound, the binder, the negative electrode conductive agent and the thickener. The present application has no special restrictions on the solvent and solid content used in the negative electrode slurry in the above step (1), as long as the purpose of the present application can be achieved. The present application has no special restrictions on the drying temperature and time in the above step (2), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the process parameters of cold pressing, cutting and slitting in the above step (4), and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no special restrictions on the size of the above-mentioned negative electrode sheet, as long as the purpose of the present application can be achieved.
[0048] The second aspect of the present application provides a secondary battery, which includes a positive electrode sheet, a separator, an electrolyte, and a negative electrode sheet in any of the above embodiments. The secondary battery of the present application has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0049] In one embodiment of the present application, the electrolyte includes a second compound, the second compound includes vinyl sulfate and / or 1,3-propane sultone, and the mass percentage of the second compound based on the mass of the electrolyte is D, 0.01%≤D≤2%. For example, the value of D can be 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or a range consisting of any two of the values. By adding the second compound of the above type to the electrolyte and regulating the mass percentage D of the second compound within the above range, the first compound and the second compound act synergistically to form a relatively stable and uniform double-layer SEI structure with an inner artificial layer and an outer natural layer on the negative electrode material layer, which is beneficial to further improve the quality of the SEI film, and the second compound is beneficial to reduce the interface resistance, improve the interface stability between the negative electrode plate and the electrolyte, thereby reducing the side reactions between the negative electrode active material and the electrolyte, reducing the continuous consumption and further decomposition of the electrolyte, thereby improving the kinetics, high temperature performance, thermal safety performance and cycle performance of the secondary battery.
[0050] In one embodiment of the present application, the electrolyte includes a third compound, the third compound includes methylene disulfonate and / or vinylene carbonate, and the mass percentage of the third compound based on the mass of the electrolyte is E, 0.01%≤E≤2%. For example, the value of E can be 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or a range consisting of any two of the values. By adding the third compound of the above type to the electrolyte and regulating the mass percentage E of the third compound within the above range, it is beneficial to form a more stable SEI film during the charge and discharge process of the secondary battery. The first compound and the third compound act synergistically to form a relatively stable and uniform double-layer SEI structure with an inner artificial layer and an outer natural layer on the negative electrode material layer, thereby reducing the side reaction between the negative electrode plate and the electrolyte. In addition, the third compound is beneficial to improving the performance of the secondary battery at high or low temperatures and increasing the application temperature range of the secondary battery. Therefore, the secondary battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0051] In the present application, the electrolyte also includes a lithium salt and a non-aqueous solvent. The present application has no particular restrictions on the lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt is 8% to 15%.
[0052] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0053] The carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), and ethyl propyl carbonate (EPC). The cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC) or butylene carbonate (BC). The fluorinated carbonate compound may include but is not limited to at least one of 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compounds may include but are not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methylcyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. The present application has no particular limitation on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent is 81% to 91.98%.
[0054] In the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive electrode current collector" means that the positive electrode material layer can be disposed on one surface of the positive electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the surface of the positive electrode current collector, or it can be a partial area of the surface of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. This application has no special restrictions on the positive electrode current collector, as long as the purpose of this application can be achieved. For example, it can include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector). The positive electrode material layer includes a positive electrode active material. The present application has no particular restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate, lithium iron manganese phosphate or lithium titanate. At least one of the positive electrode material layer may also include a conductive agent and a binder. The present application has no particular restrictions on the types of conductive agents and binders, as long as the purpose of the present application can be achieved. For example, it may be at least one of the negative conductive agent in the above-mentioned negative electrode material layer and the binder in the above-mentioned negative electrode material layer. The present application has no particular restrictions on the mass ratio of the positive electrode active material, conductive agent, and binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the positive current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved.
[0055] Optionally, the positive electrode sheet may further include a conductive layer, which is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and it can be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application does not particularly limit the conductive agent and the binder in the conductive layer, for example, it can be at least one of the conductive agent in the above-mentioned negative electrode material layer and the binder in the above-mentioned negative electrode material layer.
[0056] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of diaphragm may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0057] In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0058] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0059] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymers, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylates, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0060] In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.
[0061] The secondary battery also includes a shell for accommodating a positive electrode plate, a separator, a negative electrode plate and an electrolyte, as well as other components known in the field of secondary batteries, and this application does not limit the above-mentioned other components. This application does not particularly limit the shell, and it can be a shell known in the art, as long as the purpose of this application can be achieved. For example, the shell can be a hard shell or a flexible shell. The material of the hard shell can be metal, and this application does not limit the type of metal. A metal hard shell known in the art can be used, as long as the purpose of this application can be achieved. The flexible shell can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0062] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0063] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and there is no particular limitation in the present application. For example, the preparation process of the secondary battery may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire laminated structure with tape to obtain an electrode assembly of a laminated structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0064] The third aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0065] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0066] Example
[0067] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0068] Test methods and equipment:
[0069] Infrared spectrum test:
[0070] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the negative electrode sheet. The negative electrode sheet was soaked in dimethyl carbonate (DMC) for 30 minutes and mixed with the electrolyte collected by centrifugation. The negative electrode sheet was then baked at 100°C for 2 hours for standby use. The negative electrode material layer on the negative electrode sheet was scraped off and the powder of the negative electrode material layer was collected.
[0071] Using an infrared spectrometer (model: Nicolet iS50), the infrared spectrum of the powder of the negative electrode material layer was tested using the potassium bromide (KBr) tablet method and the liquid film method. 500 mg of KBr and 10 mg of the powder of the negative electrode material layer were ground in a mortar to obtain a mixed material. The mixed material was loaded into a pressure mold and pressurized to 20 MPa. After maintaining for 10 seconds, the pressure was released to obtain a disc; the disc was taken out and the infrared spectrum of the solid sample was tested using an infrared spectrometer. The window was cleaned with acetone, and the collected liquid sample was evenly applied to the window for testing, and the infrared spectrum of the liquid sample was tested using an infrared spectrometer. The original spectra of the solid sample and the liquid sample were pre-processed and then merged to obtain the infrared spectrum of the negative electrode material layer.
[0072] B's test:
[0073] The content of the first compound in the liquid and solid samples collected after centrifugation is tested in the same manner as the infrared spectrum test step above.
[0074] A's test:
[0075] The lithium-ion battery was discharged to 3.0V at a constant current of 0.1C, and the lithium-ion battery was disassembled to obtain the negative electrode sheet, and the negative electrode sheet was soaked in dimethyl carbonate (DMC) for 30 minutes to obtain the negative electrode sheet sample. The negative electrode sheet sample was cut into a size of 1cm×1cm, and then the cut surface of the negative electrode sheet was polished using argon plasma polishing technology (CP) to obtain a CP sample. A 1.5μm×1.5μm area was randomly selected on the CP sample as the test area, and the energy dispersive X-ray spectrometer (EDS) surface scan was performed on the test area to measure the mass percentage of carbon and silicon elements. A total of 10 test areas were tested, and the mass percentage of carbon and silicon elements was obtained by calculating the average value, and then A was calculated.
[0076] Test of component content in electrolyte:
[0077] The lithium-ion battery was discharged at a constant current of 0.5C to 2.8V and then disassembled, the electrolyte was collected, and the disassembled positive electrode sheet, negative electrode sheet, and diaphragm were centrifuged. The liquid obtained after centrifugation was evenly mixed with the above electrolyte, and then tested using a gas chromatography-mass spectrometer (instrument model: Agilent 8890) and an ion chromatography (instrument model: AQUION ion chromatography) to obtain each component in the electrolyte and test its content.
[0078] Lithium-ion acceptance testing at low temperatures:
[0079] The lithium-ion batteries in the examples and comparative examples were left to stand at 25°C for 24 hours, and then charged at a constant current of 1.0C for 1 hour, and the normal temperature charge capacity (C0) was measured. The batteries were then discharged at a constant current of 0.1C until the discharge reached 3V. The batteries were then charged at a constant current of 1.0C for 1 hour at -20°C, and the low temperature charge capacity (C1) was measured. The ratio between C1 and C0 was evaluated using the following benchmarks. The larger the value of C1 / C0, the better the lithium ion acceptance of the secondary battery at low temperatures.
[0080] When 0.65≤C1 / C0<1, it is recorded as A; when 0.5≤C1 / C0<0.65, it is recorded as B; when 0<C1 / C0<0.5, it is recorded as C.
[0081] Heat suppression safety test during internal short circuit:
[0082] The lithium-ion batteries in the examples and comparative examples were charged to an upper limit voltage of 4.5V at a constant current of 0.2C, charged to 0.05C at a constant voltage of 4.5V, and then discharged to 3.0V at a constant current method of 0.2C. The above charge and discharge steps were cycled 3 times. Then, in an atmosphere of 25°C, the upper limit voltage was charged to 4.5V at a constant current of 0.2C, and the constant voltage was charged to 0.05C at 4.5V. After that, an iron nail with a diameter of 3mm and a length of 10cm was penetrated at a speed of 5m / min through the center of the wide surface of the lithium-ion battery (one of the two planes relative to the thickness direction of the lithium-ion battery) to force it to short-circuit. The surface temperature rise of the lithium-ion battery was monitored and recorded during the process. The lower the temperature rise, the better the heat release suppression performance of the secondary battery during internal short circuit.
[0083] Coulomb efficiency test:
[0084] At 25°C, the lithium-ion batteries in the examples and comparative examples were charged to 4.5V at a constant current of 0.05C, and charged to 0.01C cutoff at a constant voltage of 4.5V, and the normal temperature charging capacity (Cx) was measured. The normal temperature charging capacity (Dx) was measured by discharging to 3.0V at a constant current of 0.05C. The above charge and discharge steps were cycled 4 times, and the charge and discharge processes from the 2nd to the 4th were taken. The charge and discharge capacities were named C1 / D1, C2 / D2, and C3 / D3, respectively. Then, the coulomb efficiency (Dx / Cx) was calculated and evaluated using the following benchmarks. The larger the coulomb efficiency, the better the uniformity of the SEI film formation of the lithium-ion battery.
[0085] Excessive gas production test:
[0086] The voltage was tested online using a Xinwei machine, and the thickness of lithium-ion batteries was tested online using Yuanneng Technology's CBS1300. Under 25°C conditions, the lithium-ion batteries in the examples and comparative examples were discharged at a constant current of 0.05C to 3.0V and then left to stand for 5 minutes, then discharged at a constant current of 10mA to 0.1C and left to stand for 30 minutes, and then discharged at a constant current of 1mA to 0.1C and left to stand for 30 minutes. During the process, the voltage and thickness (Tx) were tested online every 30 seconds, and the initial thickness was recorded as T0. Then, the thickness expansion rate (Tx / T0) of the lithium-ion battery was calculated. The smaller the thickness expansion rate at the same voltage level, the better the SEI film formation uniformity of the secondary battery.
[0087] Example 1-1
[0088] <Preparation of negative electrode sheet>
[0089] Artificial graphite and silicon-carbon material SiC are mixed together in a mass ratio of 68:2 as negative electrode active materials, and negative electrode active materials, binder styrene-butadiene rubber (SBR), thickener sodium carboxymethyl cellulose (CMC), negative electrode conductive agent carbon nanotubes, and first compound formula I-1 are mixed in a mass ratio of 95:1.2:1.1:0.2:2.5, and then deionized water is added, and stirred under the action of a vacuum mixer to form a uniform negative electrode slurry, wherein the solid content of the negative electrode slurry is 50wt%. The negative electrode slurry is coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 85°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side, and the above steps are repeated on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Then, after drying under vacuum conditions at 120°C for 12 hours, cold pressing, cutting, and slitting are performed to obtain a negative electrode sheet with a specification of 78mm×875mm. The coating weight of the negative electrode material layer during coating is 10 mg / cm 2 The compaction density of the negative electrode material layer after cold pressing is 1.7g / cm 3 .
[0090] <Preparation of positive electrode sheet>
[0091] The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent Super P, the conductive agent carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:0.8:1.2, and N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred and mixed to form a uniform positive electrode slurry, wherein the solid content of the positive electrode slurry is 72wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 9μm, and dried at 85°C to obtain a positive electrode sheet coated with a single-sided positive electrode material layer, and then the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a double-sided positive electrode material layer. Then, after cold pressing, cutting, slitting, and drying at 85°C under vacuum conditions for 4h, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the coating weight of the positive electrode material layer during coating is 19mg / cm 2 The compaction density of the positive electrode material layer after cold pressing is 4.2g / cm 3 .
[0092] <Preparation of Electrolyte>
[0093] In a dry argon environment, non-aqueous solvents ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and propyl propionate (PP) are mixed in a mass ratio of 1:1:1:1 to obtain a base solvent, and then 0.1% by mass of lithium difluorophosphate is added, dissolved and stirred thoroughly, and then lithium salt LiPF6 is added and mixed evenly to obtain an electrolyte, wherein the mass percentage of LiPF6 based on the mass of the electrolyte is 1.1%.
[0094] <Diaphragm>
[0095] A 5 μm thick polyethylene (PE) porous polymer film was used as the separator.
[0096] <Preparation of lithium-ion batteries>
[0097] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrodes to play an isolating role. Then they are wound, the pole ears are welded, placed in an aluminum-plastic film, and the electrolyte is injected. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, a soft-pack lithium-ion battery is obtained.
[0098] Example 1-2 to Example 1-19
[0099] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1. Among them, when the mass percentage of the first compound changes, the mass percentage of the negative electrode active material changes accordingly, the mass percentage of the binder, the thickener and the negative electrode conductive agent remains unchanged, and the mass ratio of artificial graphite and silicon-carbon material in the negative electrode active material remains unchanged. When the mass percentage of silicon element changes, the mass ratio of artificial graphite and silicon-carbon material in the negative electrode active material changes accordingly, and the mass ratio of negative electrode active material, binder, thickener, negative electrode conductive agent and the first compound remains unchanged. When the mass percentage of the binder changes, the mass percentage of the negative electrode active material changes accordingly, the mass percentage of the first compound, the thickener and the negative electrode conductive agent remains unchanged, and the mass ratio of artificial graphite and silicon-carbon material in the negative electrode active material remains unchanged.
[0100] Examples 1-20
[0101] Except that all the negative electrode active materials in <Preparation of Negative Electrode Sheet> are artificial graphite, the rest is the same as Example 1-1.
[0102] Example 2-1
[0103] Except that the second compound shown in Table 2 is added in <Preparation of Electrolyte>, the mass percentage of the base solvent changes accordingly, the mass ratio of each substance in the base solvent remains unchanged, and the mass percentage of lithium difluorophosphate and lithium salt LiPF6 remains unchanged, the rest is the same as Example 1-1.
[0104] Example 2-2 to Example 2-5
[0105] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 2-1. When the mass percentage of the second compound changes, the mass percentage of the base solvent changes accordingly, the mass ratio of each substance in the base solvent remains unchanged, and the mass percentage of lithium difluorophosphate and lithium salt LiPF6 remains unchanged.
[0106] Embodiment 2-6
[0107] Except that the third compound shown in Table 2 is added in <Preparation of Electrolyte>, the mass percentage of the base solvent changes accordingly, the mass ratio of each substance in the base solvent remains unchanged, and the mass percentage of lithium difluorophosphate and lithium salt LiPF6 remains unchanged, the rest is the same as Example 1-1.
[0108] Example 2-7 to Example 2-10
[0109] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 2-6. Among them, when the mass percentage of the third compound changes, the mass percentage of the base solvent changes accordingly, the mass ratio of each substance in the base solvent remains unchanged, and the mass percentage of lithium difluorophosphate and lithium salt LiPF6 remains unchanged.
[0110] Example 2-11
[0111] Except that the second compound and the third compound shown in Table 2 are added in <Preparation of Electrolyte>, the mass percentage of the base solvent changes accordingly, the mass ratio of each substance in the base solvent remains unchanged, and the mass percentage of lithium difluorophosphate and lithium salt LiPF6 remains unchanged, the rest is the same as Example 1-1.
[0112] Comparative Example 1
[0113] Except that the first compound is not added in <Preparation of Negative Electrode Plate>, the mass percentage of the negative electrode active material changes accordingly, the mass percentage of the binder, thickener and negative electrode conductive agent remains unchanged, and the mass ratio of artificial graphite and silicon-carbon material in the negative electrode active material remains unchanged, the rest is the same as Example 1-1.
[0114] Comparative Example 2
[0115] Except that the first compound of formula I-1 is replaced by ethanol in <Preparation of negative electrode sheet>, the rest is the same as Example 1-1.
[0116] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 and 2.
[0117]
[0118]
[0119] Note: “ / ” in Table 1 indicates no relevant preparation parameters.
[0120] It can be seen from Examples 1-1 to 1-20 and Comparative Examples 1 to 2 that by adding the first compound to the negative electrode material layer, the negative electrode material layer at 1050 cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm -1 and 1730cm -1 Up to 1750cm -1There are infrared characteristic peaks between the two, the value of C1 / C0 is large, the temperature rise of the lithium ion surface during short circuit is low, the value of coulomb efficiency is large, and the thickness expansion rate of the lithium ion battery is low, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium ion battery are high, thereby improving the dynamics, high temperature performance, thermal safety performance and cycle performance of the lithium ion battery. In Comparative Examples 1 to 2, there are no three characteristic peaks in the negative electrode material layer during infrared testing, or the three characteristic peaks do not appear at the same time. At this time, the value of C1 / C0 in Comparative Examples 1 and 2 is small, the temperature rise of the lithium ion surface during short circuit is high, the value of coulomb efficiency is small, and the thickness expansion rate of the lithium ion battery is high, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are poor, and the uniformity and stability of the SEI film of the lithium ion battery are poor. The lithium ion batteries in Examples 1-1 to 1-20 have good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0121] The type of the first compound usually affects the kinetics, high temperature performance, thermal safety performance and cycle performance of the lithium ion battery. It can be seen from Examples 1-1 to 1-3 that when the first compound within the scope of the present application is selected, the C1 / C0 value of the lithium ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the coulomb efficiency value of the lithium ion battery is large and the thickness expansion rate is low, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good kinetics, high temperature performance, thermal safety performance and cycle performance.
[0122] The mass percentage content B of the first compound usually affects the dynamics, high temperature performance, thermal safety performance and cycle performance of the lithium ion battery. It can be seen from Examples 1-1, 1-4 to 1-8 that when the mass percentage content B of the first compound is regulated within the scope of this application, the C1 / C0 value of the lithium ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the coulomb efficiency value of the lithium ion battery is large and the thickness expansion rate is low, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0123] The mass percentage A of silicon element usually affects the dynamics, high temperature performance, thermal safety performance and cycle performance of lithium ion batteries. It can be seen from Examples 1-1, 1-9 to 1-12 that when the mass percentage A of silicon element is adjusted within the scope of this application, the C1 / C0 value of the lithium ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the coulomb efficiency value of the lithium ion battery is large and the thickness expansion rate is low, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0124] The value of B / A usually affects the dynamics, high temperature performance, thermal safety performance and cycle performance of lithium-ion batteries. It can be seen from Examples 1-1, 1-4 to 1-12 that when the value of B / A is adjusted within the scope of this application, the value of C1 / C0 of the lithium-ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the value of the coulombic efficiency of the lithium-ion battery is large and the thickness expansion rate is low, indicating that the lithium ion acceptance of the lithium-ion battery at low temperature and the heat release suppression performance of the lithium-ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium-ion battery are high, indicating that the lithium-ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0125] The type of negative electrode active material usually affects the dynamics, high temperature performance, thermal safety performance and cycle performance of lithium ion batteries. It can be seen from Examples 1-1 and 1-13 that when the negative electrode active material within the scope of this application is selected, the C1 / C0 value of the lithium ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the coulomb efficiency value of the lithium ion battery is large and the thickness expansion rate is low, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0126] The type and content of the binder usually affect the dynamics, high temperature performance, thermal safety performance and cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-14 to 1-19 that when the binder within the scope of this application is selected and the mass percentage of the binder is adjusted within the scope of this application, the C1 / C0 value of the lithium-ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the coulomb efficiency value of the lithium-ion battery is large and the thickness expansion rate is low, indicating that the lithium-ion acceptance of the lithium-ion battery at low temperature and the heat release suppression performance of the lithium-ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium-ion battery are high, indicating that the lithium-ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0127] Whether the negative electrode active material includes silicon usually affects the dynamics, high temperature performance, thermal safety performance and cycle performance of the lithium ion battery. It can be seen from Examples 1-1 and 1-20 that when the negative electrode active material includes silicon, the C1 / C0 value of the lithium ion battery is larger, the temperature rise of the lithium ion surface during short circuit is lower, the coulomb efficiency value of the lithium ion battery is larger and the thickness expansion rate is lower, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are relatively excellent, and the uniformity and stability of the SEI film of the lithium ion battery are relatively high, indicating that the lithium ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0128] Table 2
[0129]
[0130] Note: “ / ” in Table 2 indicates no relevant preparation parameters.
[0131] The type and content of the second compound usually affect the dynamics, high temperature performance, thermal safety performance and cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 2-1 to 2-5, and 2-11 that when the electrolyte includes the second compound and the content of the second compound is within the scope of the present application, the C1 / C0 value of the lithium-ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the coulomb efficiency value of the lithium-ion battery is large and the thickness expansion rate is low, indicating that the lithium-ion acceptance of the lithium-ion battery at low temperature and the heat release suppression performance of the lithium-ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium-ion battery are high, indicating that the lithium-ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0132] The type and content of the third compound usually affect the dynamics, high temperature performance, thermal safety performance and cycle performance of the lithium ion battery. It can be seen from Examples 1-1, 2-6 to 2-11 that when the electrolyte includes the third compound and the content of the third compound is within the scope of the present application, the C1 / C0 value of the lithium ion battery is large, the temperature rise of the lithium ion surface during short circuit is low, the coulomb efficiency value of the lithium ion battery is large and the thickness expansion rate is low, indicating that the lithium ion acceptance of the lithium ion battery at low temperature and the heat release suppression performance of the lithium ion battery when an internal short circuit occurs are excellent, and the uniformity and stability of the SEI film of the lithium ion battery are high, indicating that the lithium ion battery has good dynamics, high temperature performance, thermal safety performance and cycle performance.
[0133] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0134] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0135] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material and a first compound, and the infrared spectrum of the negative electrode material layer is 1050 cm -1 Up to 1300cm -1 、1620cm -1 Up to 1680cm -1 and 1730cm -1 Up to 1750cm -1 There are infrared characteristic peaks in between.
2. The negative electrode sheet according to claim 1, wherein: The first compound includes a compound of formula I: R is selected from substituted or unsubstituted C1-C6 alkyl groups; when substituted, the substituent of the alkyl group is halogen, amino or hydroxyl.
3. The negative electrode sheet according to claim 1 or 2, wherein: The negative electrode active material includes silicon and carbon. Based on the sum of the masses of the silicon and carbon in the negative electrode active material, the mass percentage of the silicon is A, 0.1%≤A≤10%; and / or, based on the mass of the negative electrode material layer, the mass percentage of the first compound is B, 2%≤B≤5%.
4. The negative electrode sheet according to claim 3, wherein: 2%≤B≤3%。 5. The negative electrode sheet according to claim 3, wherein: 1≤B / A≤20.
6. The negative electrode sheet according to claim 2, wherein: The compound of formula I includes at least one of the following compounds:
7. The negative electrode sheet according to claim 3, wherein: The negative electrode active material further includes at least one of natural graphite or artificial graphite.
8. The negative electrode sheet according to claim 3, wherein: The negative electrode material layer also includes a binder, which includes at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyamide-imide, styrene-butadiene rubber, polyvinyl alcohol, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl butyral or aqueous acrylic resin. Based on the mass of the negative electrode material layer, the mass percentage of the binder is C, 0.65%≤C≤2.4%. 9 . A secondary battery comprising a positive electrode sheet, a separator, an electrolyte, and the negative electrode sheet according to claim 1 .
10. The secondary battery according to claim 9, wherein The electrolyte includes a second compound, the second compound includes vinyl sulfate and / or 1,3-propane sultone, and based on the mass of the electrolyte, the mass percentage of the second compound is D, 0.01%≤D≤2%.
11. The secondary battery according to claim 9, wherein The electrolyte includes a third compound, and the third compound includes methylene methanedisulfonate and / or vinylene carbonate. Based on the mass of the electrolyte, the mass percentage of the third compound is E, and 0.01%≤E≤2%. 12 . An electronic device comprising the secondary battery according to claim 9 .
Citation Information
Cited By
Negative pole piece and secondary battery
CN121726330A